Spatial interface between inhabitants and visitors in M'zab houses - Bellal, Tahar (2007)
Keywords: Urbanisme -- Mzab

Aspects de l'hellénisme dans l'Afrique du Nord antique - Desanges, Jehan (La Méditerranée d'une rive à l'autre : culture classique et cultures périphériques, 2007)
Keywords: Antiquité

Soil Aquifer Treatment Areas in Tunisia: Jerba Island - Anane, Makram; Kallali, Hamadi; Jellali, Salah; Ouessar, Mohamed (Springer, 2007)
Soil aquifer treatment (SAT) has been practiced in various dry land and semiarid areas as means to reduce environmental risk by improving wastewater quality at disposal sites and to replenish aquifers enabling the use of reclaimed water for nonrestrictive crop irrigation. SAT success is preconditioned by an appropriate site selection, a correct design, and a continuous maintenance. The location of the SAT basins is determined by a multitude of criteria often less than inituitive. This study aims to identify potential sites for SAT in Jerba Island integrating geographic information systems (GIS) tools and the analytical hierarchy process (AHP).
Keywords: Géologie -- Djerba